Odontogenic submandibular abscess in a diabetic patient with autism and incidental diffuse idiopathic skeletal hyperostosis: a case report - Tazeen, Nabeela; Ratiani, Tamar; Reddy, P. Aravind S.; Paidi, Purna C.; Paidi, Shrivatsam (International Journal of Scientific Reports, 2025)
Odontogenic infections are a leading cause of deep neck space infections, with potential to progress rapidly and cause life-threatening complications if untreated. Herein this report presents the case of a 63-year-old male with a history of diabetes mellitus, autism spectrum disorder, and tobacco chewing who developed a submandibular and sublingual abscess secondary to dental caries. The patient presented with progressive dysphagia, swelling, and fever. Laboratory investigations revealed anemia and a markedly elevated C reactive protein level, while imaging demonstrated diffuse soft tissue edema and an abscess in the left masseter muscle, along with incidental findings of diffuse idiopathic skeletal hyperostosis (DISH). Surgical incision and drainage were performed, followed by extraction of the diseased tooth and intravenous antimicrobial therapy, leading to clinical resolution. This case emphasizes the importance of early recognition and multidisciplinary management of odontogenic infections, particularly in patients with comorbidities such as diabetes and autism, and draws attention to the perioperative implications of incidental DISH in airway management.